The Efforts to Control and Prevent Cervical Cancer through Early Detection Using the VIA Test in the East Java Provincial Health Office - Riza Muhammad Zulham; Chatarina Umbul Wahyuni; Muhammad Atoillah Isfandiari; Hasan Huda (Health Notions, 2018)
Introduction:Cervical cancer is cancer that affectthe cervix and mostly (99,7%) caused by oncogenic Human Papilloma Virus (HPV). This cancer affect women who is multipara and lack of maintaining of their reproductive health. Cervical cancer cases in East Java Province in 2017 was still high and there were about 3,013 cases. This cervical cancer requiredcontrol and prevention such as screening, finding and following-up the cervical cancer cases, increasing the life quality, and decreasing mortality rate. One of cheap and quick early detection methods for screening of cervical cancer was utilizing of the VIA test method (Visual Inspection of Acetic Acid). Objective:This research aimed to analyze and solve the problem on early detection program for cervical cancer through IVA test method in Health Office of East Java Province- Indonesia. Method:The data of cervical cancer program in 2017 was collected. The data of early detection program for cervical cancer through VIA test method was analyzed and interview was conducted on health program officer and manager of the cervical cancer program to acquire the health program issues. Afterwards, the priority of the issues found on cercival cancer program was determinedusingthe Capability Accessibility Readiness Leverage (CARL) method and the alternative problem solving was determined using NGT (Nominal Group Technique) method. Conclusion:In order to achieve the early detection of cervical cancer case through VIA test method targets/indicators, Health Office of East Java Province needed to conduct network and collaboration with all of related units on the existing cervical cancer program. Health Office of East Java Province also needed to take role actively in increasing the motivation of District Health Office so that they collected and reportedthe record of non-communicable disease surveillance datawell and on time. Keywords: Control, Prevention, Cervical Cancer, CARL, NGT